Decrease in Salivary Serotonin in Response to Probiotic Supplementation With Saccharomyces boulardii in Healthy Volunteers Under Psychological Stress: Secondary Analysis of a Randomized, Double-Blind, Placebo-Controlled Trial - Karbownik, Michał Seweryn; Kręczyńska, Joanna; Wiktorowska-Owczarek, Anna; Kwarta, Paulina; Cybula, Magdalena; Stilinović, Nebojša; Pietras, Tadeusz; Kowalczyk, Edward (Frontiers in Endocrinology, 2022)
Background. Bacterial probiotics are thought to exert a serotonergic effect relevant to their potential antidepressant and pro-cognitive action, but yeast probiotics have not been tested. The aim of the present study was to determine whether 30-day supplementation with Saccharomyces boulardii affects the level of salivary serotonin under psychological stress and identify the factors associated with it. Methods. Healthy medical students were randomized to ingest Saccharomyces boulardii CNCM I-1079 or placebo before a stressful event. Salivary serotonin concentration was assessed before and at the end of supplementation. Moreover, obtained results were compared to psychological, biochemical, physiological and sociodemographic study participants data. Results. Data of thirty-two participants (22.8 ± 1.7 years of age, 16 males) was available for the main analysis. Supplementation with Saccharomyces boulardii decreased salivary serotonin concentration under psychological stress by 3.13 (95% CI 0.20 to 6.07) ng/mL, p = 0.037, as compared to placebo. Salivary serotonin was positively correlated with salivary metanephrine (β = 0.27, 95% CI 0.02 to 0.52, p = 0.031) and pulse rate (β = 0.28, 95% CI 0.05 to 0.50, p = 0.018), but insignificantly with anxiety, depression, eating attitudes and information retrieval. Conclusions. Saccharomyces boulardii CNCM I-1079 may be distinct from bacterial probiotics in its salivary serotonergic effect, which appears positively linked to symapathoadrenal markers. The study requires cautious interpretation, and further investigation.